Comparison of municipal waste management systems using LCA. South Backa waste management region. A case study - Stepanov, Jasna; Ubavin, Dejan; Prokic, Dunja; Budak, Igor; Stevanovic-Carapina, Hristina; Stanisavljevic, Nemanja (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The Republic of Serbia as a candidate country for the EU is obliged to comply with EU directives. This refers to the waste management sector as well. Different goals need to be fulfilled and the current waste management practice has to be improved in order to meet all regulatory EU requirements. Therefore, any piece of information that would support future waste management decisions is of great significance for developing and streamlining future strategies. The life cycle assessment (LCA) is a popular tool widely used for assessment of environmental impacts of waste management systems. This paper focuses on a LCA of four waste management scenarios used in selected region in Serbia (South Backa) and five indicators for the comparison and evaluation of municipal solid waste management strategies. The analysis includes the current situation of waste management in this region, as the base scenario, and three alternative scenarios. The combined life cycle inventory (LCI) model and life cycle impact assessment (LCIA) method has been used to evaluate the municipal solid waste system with the purpose of identifying environmental benefits and disadvantages, as well as economic cost of defined scenarios of waste management systems that could be implemented. The results clearly indicate the difference between the scenarios and show the influence of implementation of composting, RDF treatment, incineration and increased recycling rates on the environmental performance and economic cost of municipal solid waste management in the South Backa region.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 33-49
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma